Exploring and proclaiming the Apostles' Creed - Van Harn, Roger, 1932- (Grand Rapids, MI. W.B. Eerdmans Publishing Company, 2004)
"Doctrinal preaching has fallen on hard times in recent years. Exploring and Proclaiming the Apostles' Creed seeks to stimulate renewed interest in - and provide useful models of - Christian proclamation that is truly rooted in the central tenets of the faith. Using the Apostles Creed as a template for doctrinal, confessional preaching, this book draws together an ecumenical cast of respected biblical scholars and preachers who explain the creed and demonstrate its preaching possibilities. Each of the book's fifteen chapters consists of an essay that explores and illuminates one of the creed's articles of faith, followed by a scintillating sermon that models how that article can be preached as good news today."--Jacket.
The triune God / Marguerite Shuster -- A sermon : the triune God who seeks and finds us / Philip W. Butin -- I believe in God, the Father almighty
Includes bibliographical references.
Keywords: Apostles' Creed; Apostles' Creed -- Sermons; Doctrinal preaching; Sermons, American -- 21st century; Sermons